THE APPLICATION OF INVENTORY ACCOUNTING INFORMATION SYSTEMS AT MANUFACTURING ENTERPRISES - Marliyati Marliyati; Siti Mutmainah; Zulaika Putri Rokhimah; Novitasari Eviyanti; Retno Winarti (Applied Accounting and Management Review (AAMAR), 2022)
Accounting Information System for material inventory is a very important part for manufacturing companies to carry out supervision in order to avoid risks during the production process. Internal control over material inventory is expected to be able to reduce the possibility of collusion, human error and various other frauds on material inventory. To avoid this, it is necessary to know the internal control system for raw material inventory. Every activity that involves the inventory of materials must be guided by standard operating work procedures attached to an adequate internal control system. All management and employees of manufacturing companies have roles and responsibilities in improving the quality and implementation of the internal control system, as well as the supervisory function.